Prevalence of Obstructive Sleep Apnea in Orthodontic Patients with Different Skeletal Classes Using STOP-BANG Questionnaire: An Observational Study - Ghonim, Hany A.; Nassef, Essam M.; El Sharaby, Fouad A. (Open Access Macedonian Journal of Medical Sciences, 2021)
AIM: The aim of the study was to determine the prevalence of obstructive sleep apnea (OSA) in orthodontic adult patients with different skeletal classes and no pathology in the airway as detected from the lateral cephalometric radiographs using the STOP-BANG questionnaire. METHODS: The sample comprised 309 subjects (152 males and 157 females) collected from the Egyptian population presented to the orthodontic follicular unit extraction for treatment. The sample was divided into three groups based on the anteroposterior relationship between maxilla and mandible (ANB angle) as evident from pretreatment lateral cephalometric. Patients were asked to fill out general medical history, sign a consent form, and fill in the STOP-BANG questionnaire. Patient’s neck size and height were measured using tape measuring tool and weighing scale, respectively. Body mass index (BMI) was obtained. After submission of the questionnaire, scores were measured for each patient to evaluate the severity of OSA. RESULTS: Comparison between OSA risk in the three classes showed no statistically significant difference (p = 0.791, effect size = 0.052). CONCLUSIONS: STOP-BANG questionnaire showed that there was no statistically significant difference in the prevalence of OSA between different skeletal classes.